Birth weight concerning obesity and diabetes gene expression in healthy infants; a case-control study - Sahar Cheshmeh; Shima Moradi; Seyyed Mostafa Nachvak; Arman Mohammadi; Nastaran Najafi; Azadeh Erfanifar; Arezoo Bajelani (BMC, 2023)
Abstract Background Since obesity and diabetes are prevalent worldwide, identifying the factors affecting these two conditions can effectively alter them. We decided to investigate the expression of obesity and diabetes genes in infants with birth weights lower than 2500 g in comparison with infants with normal birth weights. Methods 215 healthy infants between the ages of 5-6 months were used in the current case-control research, which was conducted at health and treatment facilities in Kermanshah. Infants who were healthy were chosen for the research after their weight and height were measured and compared to the WHO diagram to ensure that they were well-grown and in good health. There were 137 infants in the control group and 78 infants in the case group. All newborns had 5 cc of blood drawn intravenously. To assess the expression of the genes MC4R, MTNR1B, PTEN, ACACB, PPAR-γ, PPAR-α, NRXN3, NTRK2, PCSK1, A2BP1, TMEM18, LXR, BDNF, TCF7L2, FTO and CPT1A, blood samples were gathered in EDTA-coated vials. Chi-square, Mann-Whitney U, and Spearman analyses were used to examine the data. Results A significant inverse correlation between birth weight and obesity and diabetes genes, including MTNR1B, NTRK2, PCSK1, and PTEN genes (r= -0.221, -0.235, -0.246, and − 0.418, respectively). In addition, the LBW infant's expression level was significantly up-regulated than the normal-weight infants (P = 0.001, 0.007, 0.001, and < 0.001, respectively). The expression level of the PPAR-a gene had a significantly positive correlation with birth weight (r = 0.19, P = 0.005). The expression level of the PPAR-a gene in the normal-weight infants was significantly up-regulated than the LBW infants (P = 0.049). Conclusion The expression levels of MTNR1B, NTRK2, PCSK1, and PTEN genes were up-regulated in the LBW infants; however, the expression level of PPAR-a gene was significantly down-regulated in the LBW infants compared to the infants with normal birth weight.